Measurement of the top-quark mass in all-hadronic decays in pp collisions at CDF II. - Aaltonen, T; Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; et al. (2007)
We present a measurement of the top-quark mass Mtop in the all-hadronic decay channel tt-->W+bW-b-->q1q2bq3q4b. The analysis is performed using 310 pb-1 of sqrt[s]=1.96 TeV pp[over ] collisions collected with the CDF II detector using a multijet trigger. The mass measurement is based on an event-by-event likelihood which depends on both the sample purity and the value of the top-quark mass, using 90 possible jet-to-parton assignments in the six-jet final state. The joint likelihood of 290 selected events yields a value of Mtop=177.1+/-4.9(stat)+/-4.7(syst) GeV/c2.